2005
DOI: 10.1021/es050644c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Sulfonamide Antimicrobial Agents to Clay Minerals

Abstract: Adsorption of three sulfonamide antimicrobials to clay minerals was investigated as a function of pH, ionic strength, and type of exchangeable cation. Sulfonamide antimicrobial adsorption exhibited pronounced pH dependence consistent with sorbate speciation and clay properties. Sulfonamide antimicrobials did not intercalate into montmorillonite, and surface charge density influenced sorption by determining adsorption domain size. Adsorption edge data were best fit to a model including terms for the cationic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
183
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(212 citation statements)
references
References 37 publications
17
183
3
1
Order By: Relevance
“…In general, at a lower pH, sorption of sulfonamides is enhanced primarily due to cation exchange of predominantly cationic forms of the adsorbate (17). Conversely, the observed reduction in the K D values at high pH could be attributed to the shift from cationic to anionic species of the sulfonamides, which are unavailable for cationic exchange or neutral adsorption into soil organic matter.…”
Section: Resultsmentioning
confidence: 94%
“…In general, at a lower pH, sorption of sulfonamides is enhanced primarily due to cation exchange of predominantly cationic forms of the adsorbate (17). Conversely, the observed reduction in the K D values at high pH could be attributed to the shift from cationic to anionic species of the sulfonamides, which are unavailable for cationic exchange or neutral adsorption into soil organic matter.…”
Section: Resultsmentioning
confidence: 94%
“…Recent studies have reported that sulfonamides and diaminopyrimidines showed low sorption to soils (Leal et al, 2013;Sanders et al, 2008;Srinivasan et al, 2013;Thiele-Bruhn et al, 2004). H-bonding, cation bridging, ion-exchange, surface complexes and hydrophobic partition have been shown to be the main sorption mechanisms for sulfonamides (Gao and Pedersen, 2005;Kahle and Stamm, 2007;Leal et al, 2013). However, very few studies have investigated co-sorption of sulfonamides and diaminopyrimidines which are often used together.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, an increase in ionic strength results in an increase in the sorption for both montmorillonite and kaolinite. The increase of sorption with the increase in the ionic strength maybe is due to the fact that solution ionic strength influences the double layer thickness of clays [23]. The addition of salt results in the compression of the diffuse double layer and facilitates the interaction between endrin molecules and clay surface.…”
Section: Effect Of Ph Ion Strength On Sorptionmentioning
confidence: 99%